2012
DOI: 10.1111/j.1475-3588.2012.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial hospitalization treatment for preschoolers with severe behavior problems: child age and maternal functioning as predictors of outcome

Abstract: Background This study focused on the behavioral functioning and treatment outcomes of preschool‐aged children who attended a specialized, family focused psychiatric partial hospitalization program. Method Study data were collected between 2002 and 2007. Maternal reports of child behavioral functioning were obtained at program admission and discharge. Maternal parenting stress and psychiatric impairment were assessed at admission. Results Children's symptom severity decreased from admission to discharge, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In 1 Canadian study, Grizenko and colleagues found significant improvement in externalizing problems of children who attended their 4-month program. 21 Similar findings were found with elementary-age children, 19,22,23 preschoolers, 24,25 and adolescents. 26 28 Some studies have found little to no effect though.…”
Section: Introductionsupporting
confidence: 84%
“…In 1 Canadian study, Grizenko and colleagues found significant improvement in externalizing problems of children who attended their 4-month program. 21 Similar findings were found with elementary-age children, 19,22,23 preschoolers, 24,25 and adolescents. 26 28 Some studies have found little to no effect though.…”
Section: Introductionsupporting
confidence: 84%
“…Group therapy, including family therapy, psychotherapy, wellness and substance misuse counselling, demonstrated effectiveness, notably in reducing hospital readmission rates for CYP in family-based interventions. 34 Older adolescents in these therapies exhibited diverse mental health symptoms (anxiety, autism spectrum, behavioural disorders, depression, eating disorders, psychosis, self-harm/suicidal ideation) 23 , 25 , 35 , 42 , 45 …”
Section: Resultsmentioning
confidence: 99%
“… 18 , 23 , 25 , 39 , 45 Medication, combined with other therapies, showed significant improvements in mental health symptoms, particularly for externalising symptoms (Cohen's d = 0.99) and total problems (Cohen's d = 0.86). 23 Older adolescents received pharmacotherapy for a range of mental health conditions, such as attention-deficient hyperactivity disorder, autism and depression. 18 , 25 , 39 However, some studies lacked specific medication details (type and dose) and effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Granello and colleagues found that a child and adolescent partial hospitalization program providing interdisciplinary treatment for children with Axis I diagnoses on admission produced significant reductions in attention problems, anxiety withdrawal, conduct disorder, muscle tension excess, and socialized aggression (Granello et al, 2000). Partial hospitalization programs have also been found to reduce externalizing, internalizing, and total behavior problems to a normative or nonclinical range from admission to discharge in children as young as 2 years old and as old as 19 (Martin et al, 2013; Milin et al, 2000).…”
Section: Review Of Current Outcomes Literaturementioning
confidence: 99%